POLITIK HUKUM PERUBAHAN UNDANG-UNDANG NOMOR 24 TAHUN 2003 TENTANG MAHKAMAH KONSTITUSI MENJADI UNDANG-UNDANG NOMOR 8 TAHUN 2011 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 24 TAHUN 2003 TENTANG MAHKAMAH KONSTITUSI - Ahmad, Fandi; Firdaus, Emilda; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The Constitutional Court is one of the principals of judicial power as defined in the Indonesian Constitution of 1945. Constitutional Court also referred as the guardian of the constitution which was mandated by the Indonesian Constitution of 1945. The first legislation governing the Constitutional Court is Act No. 24 Year 2003 about Constitutional Court and the latest legislation,is Act No. 8 Year 2011 on about Amendment to Law Number 24 year 2003 about the Constitutional Court. The release of Act No. 8 Year 2011, making the assumption that this law was formed due to political intervention.The purpose of this research is: first, to determine the legal politics of changes Act No. 24 year 2003 to Act No. 8 year 2011 about Amendment of the Act No. 24 year 2003 about the Constitutional Court. Second, to determine the implications of Act No. 8 year 2011 about Amendment of the Act No. 24 year 2003 about the Constitutional Court toward the Constitutional Court. Third, to determine the implications of the Constitutional Court Decision No. 49/PUU-IX/2011 toward the authority of the Constitutional Court. Research used is also called normative or literature legal research. Because using the literature as a major cornerstone in conducting this research.From this research and discussion, it is concluded that: First, The legal politics changes the Act No. 24 of 2003 about the Constitutional Court into Act No. 8 of 2011 about the Amendment of Act No. 24 Year 2003 about the Constitutional Court is with the changes occurring the Basic Law of the Constitutional Court appears that the executive and legislative changes that weaken or strengthen the authority of the Constitutional Court. Second, the implications of Act No. 8 Year 2011 to the Constitutional Court, it is change the authority of Constitutional Court. It makes weaken and strengthen the Constitutional Court. The legislator should provide reinforcement not weakens because the Constitutional Court is the only institution which has the authority to interpret the Indonesian Constitution of 1945. Third, the decision of the Constitutional Court No. 49/PUU-IX/2011 affect the Constitutional Court being the State institution which is free from the political interests of the legislators who want to control the Constitutional Court and also become the state institutions that are not supervised by other State institution.Keywords : Counstitutional Court - Legal Policy - Authority